2013
DOI: 10.1002/cbdv.201200339
|View full text |Cite
|
Sign up to set email alerts
|

Screening the Biosphere: The Fungicolous Fungus Trichoderma phellinicola, a Prolific Source of Hypophellins, New 17‐, 18‐, 19‐, and 20‐Residue Peptaibiotics

Abstract: To investigate the significance of antibiotics for the producing organism(s) in the natural habitat, we screened a specimen of the fungicolous fungus Trichoderma phellinicola (syn. Hypocrea phellinicola) growing on its natural host Phellinus ferruginosus. Results revealed that a particular group of non-ribosomal antibiotic polypeptides, peptaibiotics, which contain the non-proteinogenic marker amino acid, α-aminoisobutyric acid, was biosynthesized in the natural habitat by the fungicolous producer and, consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 103 publications
0
34
0
Order By: Relevance
“…Biological activities of 3 and 4 agreewith data from structurally closely related peptaibols, as summarized by Röhrich et al . . However, as far as we know, it seems that the antifungal activity against the human‐pathogenic A. fumigatus strain ASFU‐7 described in this paper is unprecedented.…”
Section: Discussionmentioning
confidence: 78%
“…Biological activities of 3 and 4 agreewith data from structurally closely related peptaibols, as summarized by Röhrich et al . . However, as far as we know, it seems that the antifungal activity against the human‐pathogenic A. fumigatus strain ASFU‐7 described in this paper is unprecedented.…”
Section: Discussionmentioning
confidence: 78%
“…As no amino acid analysis has been performed, a discrimination between isobaric amino acids was not possible. The diagnostic fragment ions of the peptaibols found in this study are shown in Tables S1–S4 , presented according to Röhrich et al [ 38 ]. The peptaibols produced by T. gamsii SZMC 1656 strain ( Table 1 , Figures S1, S3 and S5 ) proved to be completely different from the ones detected in the extract of T. koningiopsis SZMC 12500 ( Table 2 , Figures S2, S4 and S5 ).…”
Section: Resultsmentioning
confidence: 86%
“…H. minutispora ) and hypocitrins from T. citrinum (syn. H. citrina ) [ 38 , 48 , 49 ]. This indicates that within the genus the ability to produce 19-residue peptaibols is not restricted to clade Viride of section Trichoderma, but also occurring in sections Hypocreanum ( T. phellinicola, T. pulvinatum, T. citrinum ) and Pachybasium ( T. minutisporum ), as well as in lone lineages ( T. voglmayrii, T. gelatinosum ).…”
Section: Resultsmentioning
confidence: 99%
“…Within peptaibiotics, peptaibols represent a subgroup of non‐ribosomal, membrane‐active linear chained polypeptides characterized by a C‐terminal alcohol residue, an acylated N‐terminus and a high level of unusual amino acids, like α‐aminoisobutyric acid (Aib), 2‐isovaline (Iva), and hydroxyproline (Hyp) . Up to now peptaibols were detected either from fungal spores by intact cell mass spectrometry (ICMS) or by well‐established HPLC‐MS/MS methods after isolation from cell cultures . Based on work using MSI in the field of microbiology , our objective was to develop a sample preparation method suitable for studying Trichoderma‐Rhizoctonia interactions directly from cultivation to visualize metabolite distributions induced by mycoparasite‐host interaction to build a solid basis for future work in the field of fungal communication.…”
Section: Technical Briefmentioning
confidence: 99%